Flashlight jigsaw: an exploratory study of an ad-hoc multi-player game on public displays - Cao, Xiang; Massimi, Michael (Proceedings of the 2008 ACM conference on Computer supported cooperative work, 2008)
As large displays become prevalent in public spaces, they could be employed to create novel game experiences for the public. We present an exploratory study of an ad-hoc multi-player game played on such public displays. The game, Flashlight Jigsaw, was deployed in a shared lab space and a public atrium for two weeks in total. Through interviews supported by observations and system logs we explored the experiences and behaviors of players and spectators. We also investigated the interrelationship between public display games and the spaces they are deployed in. The research resulted in findings regarding game play, communication, social interaction, spectatorship, and space and location around such a game. We use our findings to develop design implications for future public display games.